Endothelial FGFR1 (Fibroblast Growth Factor Receptor 1) Deficiency Contributes Differential Fibrogenic Effects in Kidney and Heart of Diabetic Mice. Issue 6 (December 2020) - Li, Jinpeng; Liu, Haijie; Srivastava, Swayam Prakash; Hu, Qiongying; Gao, Rongfen; Li, Shaolan; Kitada, Munehiro; Wu, Gaosong; Koya, Daisuke; Kanasaki, Keizo
Abstract : Endothelial-to-mesenchymal transition (EndMT) has been shown to contribute to organ fibrogenesis. We have reported that N-acetyl-seryl-aspartyl- lysyl-proline (AcSDKP) restored levels of diabetes mellitus-suppressed FGFR1 (fibroblast growth factor receptor 1), the endothelial receptor essential for combating EndMT. However, the molecular regulation and biological/pathological significance of the AcSDKP-FGFR1 relationship has not been elucidated yet. Here, we demonstrated that endothelial FGFR1 deficiency led to AcSDKP-resistant EndMT and severe fibrosis associated with EndMT-stimulated fibrogenic programming in neighboring cells. Diabetes mellitus induced severe kidney fibrosis in endothelial FGFR1-deficient mice ( FGFR1 fl/fl ; VE-cadherin-Cre: FGFR1 EKO ) but not in control mice (FGFR1 fl/fl ); AcSDKP completely or partially suppressed kidney fibrosis in control or FGFR1 EKO mice. Severe fibrosis was also induced in hearts of diabetic FGFR1 EKO mice; however, AcSDKP had no effect on heart fibrosis in FGFR1 EKO mice. AcSDKP also had no effect on EndMT in either kidney or heart but partially suppressed epithelial-to-mesenchymal transition in kidneys of diabetic FGFR1 EKO mice. The medium from FGFR1-deficient endothelial cells stimulated TGFβ (transforming growth factor β)/Smad-dependent epithelial-to-mesenchymal transition in cultured human proximal tubule epithelial cell line, AcSDKP inhibited such epithelial-to-mesenchymal transition. These data demonstrated that endothelial FGFR1 is essential as an antifibrotic core molecule as the target of AcSDKP. Abstract : Supplemental Digital Content is available in the text.